Effective and selective oxidation of 2-butanol over Mn supported catalyst systems - Prabu, Kandasamy; Prabu, Marimuthu; Venugopal, Ashok Kumar; Venugopalan, Aswathy Thareparambil; Sandilya, W. V. Y. Sai; Gopinath, Chinnakonda S.; Raja, Thirumalaiswamy (Applied Catalysis A-General, 2016)
Oxidation of alcohols to their corresponding aldehydes/ketones is an important reaction in industries as well as in academic perspective. Selective oxidation (Selox) of alcohols like methanol, ethanol and propanol are well studied in literature; however, alcohols like butanol, pentanol, octanol is a challenging task. Selective oxidation of 2-butanol to methyl ethyl ketone (MEK) is an important reaction due to its wide range of applications. Herein, we demonstrated the selective oxidation of 2-butanol to MEK over Mn supported on different oxide supports. A series of MnxOy-Al2O3 (MA), MnxOy-CeO2 (MC), MnxOy-ZrO2 (MZ) and MnxOy-SiO2 (MS) catalysts were prepared by co-precipitation followed by hydrothermal method. As synthesised catalysts were characterised by various physico-chemical characterisation techniques. It was found that the presence of Mn3O4 species in MA and MZ catalysts is responsible for maximum catalytic activity towards 2-butanol oxidation. MA catalyst conferred a maximum 2-butanol conversion of 51% and 88% selectivity towards MEK. XPS analysis revealed that Mn in MA catalyst exists in +2 and +3 oxidation states and responsible for 2-butanol oxidation. Moreover it was found that the acidity of the catalyst also plays an important role in catalytic activity. (C) 2016 Published by Elsevier B.V.

Role of surface synergistic effect on the performance of Ni-based hydrotalcite catalyst for highly efficient hydrogenation of furfural - Manikandan, Marimuthu; Venugopal, Ashok Kumar; Prabu, Kandasamy; Jha, Ratnesh Kumar; Thirumalaiswamy, Raja (Journal of Molecular Catalysis A-Chemical, 2016)
The selective vapor phase hydrogenation of furfural at ambient pressure has been investigated using a facile and robust hydrotalcite derived Ni containing mixed oxide catalyst. The systematic characterization results conferred that the difficulty in the reduction of Ni species due to the strong interaction between Ni and support, which facilitated from the homogeneous distribution of hydrotalcite structure. It was also found that the structure and catalytic performance of the catalysts were greatly influenced by Ni loading. Through fine-tuned surface elemental sites and reaction conditions, furfural conversion of 98% with 95% of furfuryl alcohol selectivity was achieved over a MAN-2 catalyst containing two molar ratio of Ni. The results have demonstrated that the incorporation of Mg significantly enhances the Ni-support interaction, Ni dispersion and catalytic performance. The high efficiency of the Ni-based hydrotalcite derived catalyst was mainly attributed to the surface synergistic interaction between the catalytically active metallic Ni sites and the strong basic sites, which furnished an eco-benign and sustainable catalyst for the selective hydrogenation of furfural. Furthermore, the spent catalyst analysis substantiated that no significant difference in the catalyst phase was observed even after 48 h of reaction stream. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: alcohol-hydrotalcites-selective; Biomass-frurfural-furfuryl; Hydrogenation